A chemical approach to the adhesion ability of cement-based mortars with metakaolin applied to solid substrates. (15th April 2023) - Lima, N.B.; Silva, D.; Vilemen, P.; Nascimento, H.C.B.; Cruz, F.; Santos, T.F.A.; Oliveira, R.; Póvoas, Y.; Padron-Hernández, E.; Lima, N.B.D.
Abstract: Chemical interactions in cement-based materials affect important properties, such as mechanical performance. In this sense, a simple theoretical model based on the strength of hydrogen bonds and SiO2 /(Ca(OH)2 stoichiometric ratio is employed to advance a chemical approach to the adhesion ability of mortars with metakaolin applied to solid substrates (concrete and roughcast/concrete). To evaluate the robustness of the theoretical model, the investigated mortars were prepared, and tests of XRD, SEM, stereoscopy, and adhesion resistance were performed. The results revealed that the model was useful in predicting aspects of the adhesion capacity of the mortars with metakaolin. In addition, the XRD and SEM results showed the presence of important phases in the microstructures of the investigated mortars, such as Portlandite and CSH . Further, the tests of adhesion strength agreed with the predicted by the simple theoretical model, in which: similar average values were obtained to reference, and the mortars prepared with the addition of metakaolin, that are higher than the corresponding adhesion strengths of the mortars prepared with cement replaced by metakaolin. The stereograms of the rupture interfaces revealed a non-homogeneous adhesion when the mortar is directly applied to the concrete substrate and a homogeneous adherence when the mortar is applied to roughcast/concrete substrate. Finally, from a molecular chemistry perspective, the role of the roughcast in the adherence mechanism is to facilitate the transfer of hydrogen bonds in the sense of the mortar to the concrete substrate. Highlights: A chemical approach to the adhesion of mortars applied to concrete surfaces is advanced. The ability of the mortars to form hydrogen bonds is associated with the process of water diffusion. The addition of metakaolin does not significantly affect the hydrogen bond strength. The replacement of cement by metakaolin affects the strength of hydrogen bonds. The ability of the mortars to transfer hydrogen bonds affects their adhesion strength.